PENYULUHAN TENTANG MENANGGULANGI UJARAN KEBENCIAN DI SMA SANTA THERESIA JAKARTA - Roswita Oktavianti; Lusia Savitri Setyo Utami (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2019)
Abstract. Hate speech messages in social media and instant messaging services that are increasingly widespread have the potential to threaten the unity of the nation. Hate speech messages not only seek to instigate and influence a person but also disunite the people of Indonesia. The younger generation as the active users of social media and instant messaging is considered vulnerable to the exposure of hate speech messages. Therefore, the community service team of Faculty of Communication Tarumanagara University conducted counseling to Santa Theresia High School students in Central Jakarta about the prevention of hate speech. It aims to provide understanding to high school students about hate speech so that they can identify messages with hate speech nuances and know how to encounter them. After the counseling, the results show that the digital generation as the high social media and instant messaging users with hate speech messages are able to identify the hate speech messages that they receive in both social media and instant messaging services. They can also consider that hate speech messages are not a form of freedom of speech.Key words: hate speech, social media, instant messaging Abstrak. Pesan ujaran kebencian (hate speech) di media sosial dan layanan pesan instan yang semakin marak berpotensi mengancam persatuan kesatuan bangsa. Ujaran kebencian tidak hanya berupaya menghasut dan mempengaruhi seseorang tetapi juga memecah belah masyarakat Indonesia. Generasi muda sebagai pengguna aktif media sosial dan pesan instan rentan dengan terpaan pesan ujaran kebencian. Atas dasar itulah, tim pengabdian kepada masyarakat Fakultas Ilmu Komunikasi Universitas Tarumanagara melakukan penyuluhan kepada siswa SMA Santa Theresia Jakarta Barat tentang penanggulangan ujaran kebencian. Tujuannya adalah memberikan pemahaman kepada siswa SMA tentang ujaran kebencian, sehingga mampu mengidentifikasi pesan-pesan bernuansa ujaran kebencian dan cara menanggulanginya. Setelah penyuluhan, survei menunjukkan generasi muda sebagai generasi digital dengan kondisi tingginya penggunaan media sosial dan pesan instan, mampu mengidentifikasi pesan-pesan ujaran kebencian yang mereka terima baik di media sosial maupun layanan pesan instan. Generasi ini juga menilai bahwa ujaran kebencian bukan bentuk dari kebebasan berbicara.Kata Kunci: Ujaran kebencian, media sosial, pesan instan